2017
DOI: 10.18632/oncotarget.15054
|View full text |Cite
|
Sign up to set email alerts
|

Over-expression of Thrombospondin 4 correlates with loss of miR-142 and contributes to migration and vascular invasion of advanced hepatocellular carcinoma

Abstract: Hepatocellular carcinoma (HCC) is a common malignancy found worldwide and is associated with a high incidence of metastasis and vascular invasion. Elucidating the molecular mechanisms that underlie HCC tumorigenesis and progression is necessary for the development of novel therapeutics. By analyzing the Cancer Genome Atlas Network (TCGA) dataset, we identified Thrombospondin 4 (THBS4) is significantly overexpressed in HCC samples and is correlated with prognosis. Overexpression of THBS4 was also highly correla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
39
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 28 publications
1
39
0
Order By: Relevance
“…High expression of TSP4 in remodeling tissues, particularly in heart disease and cancer [5][6][7][8][9][10][11][12][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29], suggested that this matricellular protein may regulate fibrosis and angiogenesis. The effects of TSP-4 on matrix remodeling has been demonstrated in Thbs4 -/mice by us and others [5][6][7]45], and we recently reported that TSP4 is pro-angiogenic [24,25] in contrast to the prominent role of TSP-1 as an anti-angiogeneic protein [2,54,55].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…High expression of TSP4 in remodeling tissues, particularly in heart disease and cancer [5][6][7][8][9][10][11][12][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29], suggested that this matricellular protein may regulate fibrosis and angiogenesis. The effects of TSP-4 on matrix remodeling has been demonstrated in Thbs4 -/mice by us and others [5][6][7]45], and we recently reported that TSP4 is pro-angiogenic [24,25] in contrast to the prominent role of TSP-1 as an anti-angiogeneic protein [2,54,55].…”
Section: Discussionmentioning
confidence: 99%
“…High levels of TSP4 have been detected in remodeling and failing hearts [3][4][5][6][7], several cancers [8][9][10][11][12][13], and atherosclerotic lesions [14]. Recently, new functions have been ascribed to TSP4 in cardiovascular system [5][6][7][14][15][16][17][18][19][20][21][22][23][24][25], cancer [8][9][10][11][12][24][25][26][27][28][29], and nervous system [30][31][32][33][34], but effects of TSP4 on cellular responses and the regulation of TSP4 expression remain poorly understood. For example, with an exception of TGF-beta [25], stimuli inducing TSP4 expression in tissues remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…High levels of TSP-4 have been detected in remodeling and failing hearts [3][4][5][6][7] , several cancers [8][9][10][11][12][13] , and atherosclerotic lesions 14 . Recently, new functions have been ascribed to TSP-4 in the cardiovascular system [5][6][7][14][15][16][17][18][19][20][21][22][23][24][25] , cancer [8][9][10][11][12][24][25][26][27][28][29] , skeletal muscle 30,31 , and nervous system [32][33][34][35][36] , but effects of TSP-4 on cellular responses and the regulation of TSP-4 expression remain poorly understood. For example, with an exception of TGFbeta 25 , stimuli inducing TSP-4 expression in tissues remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…The breast-related gene explored by Huang et al [32] contains the gene THBS4, which is up-regulated in breast cancer. In the study of hepatocellular carcinoma, Su et al [33] found that knockdown of ThBS4 inhibited migration and invasion of hepatocellular carcinoma cells, as well as hemangiocarcinoma-induced angiogenesis. THBS4 as a target is very promising for the treatment of advanced liver cancer.…”
Section: Discussionmentioning
confidence: 99%